Performance analysis of mono-crystalline and poly-crystalline silicon solar cells under different climatic conditions : a comparative study - Roy, Shuvajit; Sharmin, Raisa Sadat; Ferdous, Tajkia (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.